Te Toi o Matariki: A Cultural Model for Personal Growth and Development - Iwikau, Betty-Lou (Auckland University of Technology, 2007)
There is a greater recognition by Māori of the potentially harmful effects of alcohol and drugs. However there are concerns about the patterns of use and the rising incidence of alcohol and drug related risks such as; hospital admissions, domestic abuse, and alcohol and drug related convictions. As a result alcohol and drug use among Māori is a major threat to their health and well being. Consequently there is a need for models that are culturally appropriate to effectively address the problem. In New Zealand there is an increase in the use of customary Māori values, beliefs and practices in the treatment of Māori with substance abuse. This has also involved the integration of Western approaches and treatment modalities that are beneficial to Māori. However, the main purpose of the research is to give credence to Te Toi o Te Matariki model within the clinical setting. It is anticipated that the outcomes will inspire confidence in cultural model of practice in personal growth and development for Maori people who present with substance abuse. Te Toi o Te Matariki model is examined in the context of the Te Ara Hou residential drug and alcohol programme, a service provided by Raukura Hauora o Tainui (RHOT) in Auckland. The analogy is "to ascend or achieve to the highest point of the Whare Wananga (house of learning) so that the best view or position in the world is gained." It demonstrates three stages of continuous layers and has been developed in accordance with the key principles of the whakapapa (genealogy) paradigm of Te Kore, Te Po and Te Ao Marama. These principles form the infrastructure of the programme.
Keywords: Te Toi o Matariki